The Bigger the Better? Analysis of Surgical Complications and Outcome of the Retrosigmoid Approach in 449 Oncological Cases - Aftahy, Amir Kaywan; Jörger, Ann-Kathrin; Hillebrand, Sandra; Harder, Felix N.; Wiestler, Benedikt; Bernhardt, Denise; Combs, Stephanie E.; Meyer, Bernhard; Negwer, Chiara; Gempt, Jens (Frontiers in Oncology, 2022)
Introduction: Exposure to the posterior skull base and the cerebellopontine angle is challenging due to important neurovascular structures. The retrosigmoid approach (RSA) has become its workhorse approach. We report our experiences with RSAs regarding technical obstacles, complications, and approach-related outcomes. Materials and Methods: We performed a retrospective chart review at a tertiary neurosurgical center between January 2007 and September 2020. We included all patients undergoing surgery for oncologic lesions through RSAs, concentrating on surgical technique, postoperative outcome, and complications. Results: 449 RSAs were included. The median age at the time of surgery was 58 years; 168 (37.4%) were male and 281 (62.6%) females. The median approach surface was 7.8 cm2. The median tumor volume was 5.9 cm3. The Median Clavien-Dindo grade was 2, the total complication rate was 28.7%, and GTR was 78.8%. Findings revealed that tumor volume had no significant impact on postoperative complications in general (P = 0.086), but on postoperative hemorrhage (P = 0.037) and hydrocephalus (P = 0.019). Tumor volume was significant for several preoperative symptoms (P < 0.001). The extent of approach had no significant impact on complications in general (P = 0,120), but was significant regarding postoperative CSF leaks (P = 0,008). Craniotomy size was not significant regarding GTR (P = 0.178); GTR rate just missed significant correlation with tumor volume (P = 0,056). However, in the case of vestibular schwannomas size of craniotomy was important for GTR (P = 0.041). Conclusion: Tumor volume has an important impact on preoperative symptoms as well as on postoperative complications. Although the extent of the craniotomy barely missed significance regarding GTR, a correlation can be assumed. Thus, the extent of craniotomy should be taken into presurgical consideration, especially in the case of postoperative CSF leaks. Regarding vestibular schwannomas, craniotomy size plays an important role to achieve satisfactory oncological outcomes. Bigger approaches should be selected where necessary regarding superior resection rates.